Advertisement
Guest User

set

a guest
Aug 29th, 2015
74
0
Never
Not a member of Pastebin yet? Sign Up, it unlocks many cool features!
text 1.02 KB | None | 0 0
  1. Premises:
  2. (tim --> cat).
  3. ((&&,($1 --> cat),($1 --> [orange])) ==> ($1 <-> garfield)).
  4.  
  5. Rule:
  6. (S --> M), ((&&,($1 --> M),A_1..n) ==> B), substitute($1,S) |- ((&&,A_1..n) ==> B)
  7.  
  8. Match Process:
  9. M:={}, P={}
  10.  
  11. MATCH Step1:
  12.  
  13. Unify (S --> M) with (tim --> cat) under M
  14. => M={S -> tim, M -> cat}
  15.  
  16. MATCH Step2:
  17. Unify ((&&,($1 --> M),A_1..n) ==> B) with ((&&,($1 --> cat),($1 --> [orange])) ==> ($1 <-> garfield)) under M
  18. => M={S -> tim, M -> cat, A_1 -> ($1 --> [orange]), B -> ($1 <-> garfield)}
  19.  
  20. MATCH Step3:
  21. Satisfy substitute($1,S) by applying the subsitutions in M to substitute($1,S) leading to substitute($1,tim),
  22. this substitution is added to the substitution set P:
  23. => P={$1 -> S}
  24.  
  25. "Construction of Conclusion" Step4:
  26. The match process is finished, and was satisfyable, now lets build the conclusion
  27. by applying at first M to the conclusion ((&&,A_1..n) ==> B) specified by the rule
  28.  
  29. leading to:
  30.  
  31. (($1 --> [orange]) ==> ($1 <-> garfield))
  32.  
  33. now we apply P and get:
  34.  
  35. ((tim --> [orange]) ==> (tim <-> garfield))
Advertisement
Add Comment
Please, Sign In to add comment
Advertisement